Application of Modal Superposition Technique in the Fatigue Analysis Using Local Approaches. (2016) - Horas, C. Silva; Correia, J.A.F.O.; De Jesus, A.M.P.; Calçada, R.; Aenlle, M.L.; Kripakaran, P.; Pelayo, F.; Fernandez-Canteli, A.
Abstract: The fatigue analysis of materials and structural details using local approaches, such as, stress-life, strain-life or energetic approaches, are important to estimate the fatigue crack initiation at notches. Various engineering structures, such as, bridges, wind towers, among others are subjected to cyclic dynamic loading which may substantially reduce the strength of these structures. Nowadays, the structures tend to be more complex and it is necessary to find computationally efficient solutions to perform their fatigue analysis, for dynamic actions corresponding to long complex loading events (e.g. diversity of trains crossing a bridge). Thus, this paper aims at presenting a generalization of a methodology based on modal superposition technique for local fatigue damage parameters evaluation, which could be applied in fatigue analysis using local approaches. This technique was applied recently in the context of fracture mechanics based fatigue crack propagation. But the modal superposition technique can be extended to compute the history of local notch stresses and deformations at notches. In addition, the technique can be explored for the case of local confined plasticity at notches where global elastic behavior of the component still prevails. Local submodeling can be explored with this technique to avoid the necessity of large computational models. Local models are only required to be run only for the selected modal shapes of the structure, the local time history of fatigue damage variable being reconstructed by modal superposition for each loading event.